Analisis Quality of Service (QOS) pada Akses Game Online Menggunakan Standar Tiphon - Bambang Nakulo; Chanief Budi Setiawan; Rama Sahtyawan; M. Abu Amar Al Badawi (Jurnal Teknomatika, 2022)
The quality of internet service plays a crucial role in online gaming experiences. This study focuses on assessing the quality of internet services provided by 6 cellular cards in Indonesia using the TIPHON standard. The objective is to determine the suitability of these services for online gaming on a website. Data packets generated during online gaming sessions were captured using the Wireshark application in three different locations. The captured data was processed using the TIPHON standard formula to evaluate the quality of internet service provided by the 6 cellular cards. The analysis of the captured data revealed that three cellular cards, namely Telkomsel, XL, and Tri, demonstrated good performance in terms of providing a quality online gaming experience. The results were consistent across the three tested locations. Based on the TIPHON standard, the evaluation of 6 cellular cards in three different locations indicated that three of them (Telkomsel, XL, and Tri) offer suitable internet service for playing online games on the website.